Needs of learners with disability: inputs in promoting inclusive education - Estillore, John O.; Arante, Ramil B. (Intelektual Pustaka Media Utama, 2026)
This study explored the critical needs of learners with disabilities and their impact on promoting inclusive education. With the growing emphasis on creating equitable learning environments, it is essential to understand the unique challenges and requirements faced by learners with disabilities in the context of Caraga State University Cabadbaran Campus, an educational institution based in the Philippines. Through a sequential exploratory mixed-methods approach, which includes surveys of 900 participants out of 3,000 enrolled learners and interviews with 10 participants from 61 learners with disabilities based on the survey results, the study identified critical needs essential for their academic growth. These are academic needs, social integration and identity needs, preferred learning environment, peer support and learning assistance needs, inclusivity and equity needs, and a supportive learning environment. These needs suggest that a holistic approach integrating mental health, financial aid, inclusivity, peer assistance, and personalized learning can significantly improve the educational experiences of learners with disabilities, promoting a more equitable and supportive learning environment. These findings also serve as inputs to guide educational institutions toward more inclusive practices, ensuring that learners with disabilities are given equal opportunities to succeed academically. Addressing their needs contributes to the ongoing efforts to promote inclusive education in higher education institutions, fostering a more supportive and accommodating environment for all learners.